Advancing Equitable Access to Medicines in Southeast Asia: A Comprehensive Policy Analysis of the 2025 Regional Position Paper - Mayadhar Sethy* (International Journal of Social Science and Community Service, 2026)
The Southeast Asia region faces persistent challenges in ensuring equitable access to affordable, quality medicines despite decades of economic growth and health system advancements. This article provides a comprehensive policy analysis of the "Advancing Equitable Access to Medicines in Southeast Asia" position paper released by the Southeast Asia Access to Medicine Working Group following the February 2025 Bangkok Summit and April 2025 New Delhi consultations. The analysis examines the paper's conceptual framework that redefines access as a patient-centered continuum, evaluates its recommendations across five core pillars; governance, digital health, health technology assessment, innovative financing, and public-private partnerships and assesses implementation feasibility within ASEAN's diverse contexts. Findings reveal that while the position paper offers transformative strategies emphasizing regional harmonization and community engagement, successful implementation requires navigating significant challenges including regulatory fragmentation, varying institutional capacities, sustainable financing mechanisms, and political economy constraints. The analysis employs health systems frameworks and political economy analysis to identify critical success factors for translating policy recommendations into measurable improvements. The article concludes that realizing equitable access demands sustained political commitment, institutionalized cross-sector collaboration, adaptive governance frameworks, and robust monitoring systems. The study contributes to policy discourse by identifying critical research gaps including the need for context-specific implementation metrics, longitudinal impact assessment frameworks, and participatory governance evaluation tools.